A glimpse of the future of healthcare at the seaside. (28th March 2011) - Davies, Peter
Abstract : Combining health and social care at a seaside authority on the south coast of England has proved so successful it's prompted the NHS chief executive to anoint it as "the future." Peter Davies investigates